LATAR SEBAGAI SIMBOL KETIDAKADILAN GENDER DALAM RAISE THE RED LANTERN - Resti Nurfaidah (Madah: Jurnal Bahasa dan Sastra, 2016)
Raise the Red Lantern is one of Su Tong’s masterpiece. He is a famous writer in China. Su Tong had high technique in writing the novel with his a controversial way for talking about taboo. The novel has been modified into a movie of the same title. Both forms, the novel and the film, also could need different techniques. The novel need high technique of composing words accurately so the reader can be involved into the story. Meanwhile, the film is dominated by picture. Taking the camera and the mixing process requires high precision so that the viewers can be enjoyable in the spectacles. This paper describes theconcept of the novel and the film Raise the Red Lantern from both settings. There are some significant differences were found in both data sources, among other things, the death of Yan'er, places and stages of the execution of the Third Wife, placing the main focus on the Chinese traditional lanterns in front of the gate whose visited wife, and Songlian latest condition. Those were analysed based on the concept of setting, gender, semiotics, and cinematographic.